Using trial follow-up surveys to assess varietal adoption: The case of beans - David, S.; Wortmann, Charles S.; Kasozi, S; Mugisha-Mutetikka, M (1997)
Drawing on results of a survey of Ugandan farmers who previously hosted bean (Phaseolus vulgaris L.) varietal trials, this paper reports on the adoption of three new bush bean cultivars and assesses the usefulness of post-trial surveys as a methodology for obtaining reliable early feedback on varietal adoption potential. While this case study confirms the validity of post-trial surveys for verifying varietal acceptance and predicting broad trends in varietal adoption, the findings from such studies should be assessed within the context of the complexity of choices farmers make about seed use, which are not solely an expression of their varietal preference, especially among the poorest farmers. The negative implications of adverse agro-environmental conditions for the retention of seed of new varieties and hence, adoption, are clearly highlighted. The study also warns against the pitfalls of making wider inferences from the adoption behaviour of trial farmers, since the experimentation process itself may interfere, positively or negatively, with the adoption process.